A Comparison of Inclusive versus Resource Classroom Placement for Black Students with Mild Disabilities at the Secondary Level: Is There a Need for Separation? - Graham, Earle; Lawson, Carl; Rasheed, Saleem A.; Voltz, Deborah (Journal of the American Academy of Special Education Professionals, 2007)
The purpose of this study was to determine whether Black students with mild disabilities receiving their education in general education settings perform better academically than Black students with mild disabilities receiving their education in resource classroom settings. Sixty-four Black high school students with mild disabilities receiving special education services were assessed using the Grade Level Short Form (Reading sub-test) of the Multilevel Academic Survey Test (MAST). Their reading scores were examined relative to each participant’s placement in either included or non-included classrooms. Results revealed statistically significant evidence of difference in reading abilities to indicate that one group outperformed the other group in the inclusive or resource classroom settings. Limitations of the study, implications for both general and special educators, and considerations for future research are discussed.